Pengaruh Debt to Equity Ratio, Return On Equity dan Total Asset Turnover Terhadap Price to Book Value (Pada Perusahaan Properti dan Real Estate Yang Terdaftar di Bursa Efek Indonesia Tahun 2019 – 2024) - Rohiman, Rohiman; Kusumawardani, Astrin; Herlina, Listri (IKRAITH-EKONOMIKA, 2026)
This study aims to examine the effect of Debt to Equity Ratio (DER), Return on Equity (ROE), and Total Asset Turnover (TATO) on Price to Book Value (PBV) in property and real estate companies listed on the Indonesia Stock Exchange from 2019 to 2024. This research was conducted due to economic uncertainty and market fluctuations that affect the value of the property and real estate sector. The method used is multiple linear regression analysis. Secondary data was obtained from audited annual financial reports, and the analysis was conducted using SPSS version 26. The results show that DER and ROE have a positive and significant effect on PBV, while TATO is not significant. Therefore, property and real estate companies are advised to increase DER and ROE as strategic financial objectives to enhance company value and attract investor interest in a competitive capital market.